Achromatic diffractive lens written onto a liquid crystal display - Márquez, A. (2006)
We propose a programmable diffractive lens written onto a liquid crystal display (LCD) that is able to provide equal focal lengths for several wavelengths simultaneously. To achieve this goal it is necessary that the LCD operate in the phase-only regime simultaneously for the different wavelengths. We design the appropriate lens for each wavelength, and then the lenses are spatially multiplexed onto the LCD. Various multiplexing schemes have been analyzed, and the random scheme shows the best performance. We further show the possibility of finely tuning the chromaticity of the focal spot by changing the relative weights of the multiplexing among the various wavelengths.